2012
DOI: 10.1097/iae.0b013e31824fd384
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intraocular Pressure Elevation After Anterior Versus Posterior Subtenon Triamcinolone Acetonide Acetate Injection

Abstract: An ASTI of triamcinolone acetonide may bear a higher risk of developing elevated IOP than a PSTI of triamcinolone acetonide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…As in the present study, IOP elevation after treatment with 20 mg STTA was observed in 7/85 eyes (8.2%) [7] and 8/48 eyes (16.7%) [34]; IOP elevation after treatment with 40 mg STTA was observed in 6/49 eyes (12%) [41], 6/35 eyes (17%) [5], and 26/115 eyes (22.6%) [42].…”
Section: Discussionsupporting
confidence: 78%
“…As in the present study, IOP elevation after treatment with 20 mg STTA was observed in 7/85 eyes (8.2%) [7] and 8/48 eyes (16.7%) [34]; IOP elevation after treatment with 40 mg STTA was observed in 6/49 eyes (12%) [41], 6/35 eyes (17%) [5], and 26/115 eyes (22.6%) [42].…”
Section: Discussionsupporting
confidence: 78%
“…[ 8 9 10 20 ] Furthermore, PSTA showed 2.4 times lower risk of associated IOP elevation than anterior subtenon triamcinolone injection. [ 21 ] Therefore, we added PSTA on routine IVR for these refractory diabetic patients, in order to enhance the efficacy of macular edema control and lower the possibility of postinjection ocular hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature reported that an anterior subtenon injection of TA was 2.4 times more likely (95% CI, 1.02-5.9) to cause elevated IOPs than a posterior subtenon injection 16 . A higher level of aqueous humor triamcinolone may be associated with a higher incidence of IOP elevation.…”
Section: Iopmentioning
confidence: 90%